ANALYSIS OF FACTORS AFFECTING INTEREST IN BUYING 5 KG LPG AT PT. TWO PUTRI LATJINTA KENDARI - Djauhar, Asri; Ningsi, Jumria; Zainuddin, Zainuddin; Manan, La Ode ABdul (Sultra Journal of Economic and Business, 2022)
This study aims to determine the factors that influence buying interest in 5 kg LPG at PT. Two Princesses of Latjinta Kendari. The sample in this study were 40 respondents who used and purchased 5 kg LPG gas cylinders at PT. Two Princesses of Latjinta Kendari. This study uses multiple linear regression analysis as an analytical tool. The results of the study found that partially price, promotion and service quality had a positive and significant effect on buying interest. Simultaneously price, promotion and service quality have a positive and significant effect on buying interest.